Japanese Orange Fly, Bactrocera tsuneonis (Miyake) (Insecta: Diptera: Tephritidae) - Howard V. Weems, Jr.; Thomas R. Fasulo (EDIS)
The Japanese orange fly, Bactrocera tsuneonis (Miyake), is one of the most important pests of citrus in Japan. Extensive outbreaks have occurred in some commercial citrus areas since 1947 when up to 60 percent or more of the fruits were infested. This fruit fly has also been reported to have infested 50 percent of the oranges at Kiangtsin, in the Szechwan Province of southwestern China during 1940. There have been no interceptions of the Japanese orange fly in the United States, probably due in a large part to the protection provided by a US embargo of long standing against citrus from the orient.This document is EENY-263 (originally published as DPI Entomology Circular 56), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2002.